Life Stories and Sociological Imagination : Music, Private Lives, and Public Identity in France and Sweden. - D''Urso, Alexandra (Cambridge Scholars Publishing, 2013)
What happens when public figures' private selves are put forth for examination by public audiences? How do the personal struggles of music artists, specifically those with immigrant backgrounds, compare to the private struggles of other individuals? At a time when many countries in the European Union are experiencing an increase in far-right political party activities, how do individuals from the margins negotiate new ways of thinking about identity, offering hope for a greater understanding ...